Collaborative Policing In The Post-Truth Era: A Study On The Role Of The Indonesian National Police (Polri) In Addressing Identity Politics And National Stability During The 2017, 2019, And 2024 General Elections - Sindhu, R. Martono; S, Gumilar Rusliwa; Thamrin, Djuni (Program Pascasarjana Universitas Negeri Makassar, 2025)
The growing phenomenon of identity politics in the post-truth era has transformed Indonesia’s democratic landscape, where emotional narratives and disinformation spread through social media have replaced rational political discourse. During the 2017, 2019, and 2024 general elections, the politicization of ethnicity, religion, race, and societal groups (SARA) became a normalized electoral strategy among political actors, posing a serious threat to social cohesion and national stability. This condition highlights the need for developing a new, collaborative, and adaptive policing model in response to the challenges of the digital era. The objectives of this research are to: (1) analyze the process of identity politics production in the post-truth era within the context of Indonesia’s general elections; (2) explain the impact of identity politics on national security stability and the institutional role of the Indonesian National Police (Polri); and (3) formulate an effective and innovative Collaborative Policing Model based on inter-agency synergy and strategic communication approaches to mitigate the escalation of identity politics in the post-truth era and to strengthen social resilience and national stability. This study employs a qualitative approach with a case study method, drawing on in-depth interviews with Polri officials, relevant ministries, and civil society organizations, alongside document analysis and digital content review. The findings reveal that conventional policing models, such as Community Policing and Democratic Policing, have positively contributed to maintaining social order but remain insufficiently adaptive to the complexity and velocity of digital disinformation dynamics. To address these gaps, the study proposes an Innovative and Effective Collaborative Policing Model built upon three key pillars: (1) Inter-agency Synergy, positioning Polri as the leader of collaborative security governance that integrates Community Policing, Democratic Policing, and Digital Restorative Justice; (2) Trust-Based Strategic Communication, emphasizing transparency, accountability, and public empathy as the foundation of police legitimacy and risk-communication-oriented practices; and (3) Real Time – Trust Based Policing, which utilizes information dromology and real-time data analytics accountable to public audit mechanisms. This model contributes both theoretically and practically to the development of a new paradigm of policing in the post-truth era one that balances national security with democratic accountability, digital ethics, and collaborative governance rooted in public trust.